RETRACTED: Design, Synthesis, and Biological Evaluation of (E)-N'-((1-Chloro-3,4-Dihydronaphthalen-2-yl)Methylene)Benzohydrazide Derivatives as Anti-prostate Cancer Agents - Arjun, H. A.; Elancheran, Ramakrishnan; Manikandan, N.; Lakshmithendral, K.; Ramanathan, Muthiah; Bhattacharjee, Atanu; Lokanath, N. K.; Kabilan, Senthamaraikannan (Frontiers in Chemistry, 2019)
Prostate Cancer (PCa) is the most frequently diagnosed cancer in man in the late '50s. PCa growth is mainly due to the activation of androgen receptor by androgens. The treatment for PCa may involve surgery, hormonal therapy, and oral chemotherapeutic drugs. Structural based molecular docking approach revealed the findings of (E)-N'-((1-chloro-3,4-dihydronaphthalen-2-yl)methylene)benzohydrazide derivatives, where the possible binding modes of the compounds with protein (PDB ID: 3V49) are shown. The compounds (6a-k) were synthesized and characterized well by using conventional methods. The compounds, 6g, 6j and 6k were reconfirmed through single crystal X-ray diffraction (XRD). Further, the compounds (6a-k) and standard drug were evaluated against human prostate cancer cell lines, LNCaP and PC-3 and non-cancerous cell line, 3T3. Among these compounds, 6g and 6j showed a higher cytotoxicity, and 6g exhibited dose-dependent activity and reduced cell viability. The mechanism of action was observed through the induced apoptosis and was further confirmed by western blot and ELISA. Molecular dynamics simulations studies were carried out to calculate the interaction and the stability of the protein-ligand complex in motion. ADME properties were predicted for all the tested compounds. These findings may give vital information for further development.